2016
DOI: 10.1145/2946838
|View full text |Cite
|
Sign up to set email alerts
|

Using Respiration to Predict Who Will Speak Next and When in Multiparty Meetings

Abstract: Techniques that use nonverbal behaviors to predict turn-changing situations—such as, in multiparty meetings, who the next speaker will be and when the next utterance will occur—have been receiving a lot of attention in recent research. To build a model for predicting these behaviors we conducted a research study to determine whether respiration could be effectively used as a basis for the prediction. Results of analyses of utterance and respiration data collected from participants in multiparty meetings reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 20 publications
2
45
2
Order By: Relevance
“…Furthermore, we had predicted speech activity for each respiratory cycle, whereas in the current work predictions are made every 100 ms, from the beginning of the conversation to its end. In this second respect, the current article also extends the work in [2], where predictions were made only at turn landmark locations. In addition, unlike the authors of [2], who compared their system to a random baseline, the current article compares the contribution of breathing in the context of multi-participant speech activity to a baseline trained on multi-participant speech activity alone.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…Furthermore, we had predicted speech activity for each respiratory cycle, whereas in the current work predictions are made every 100 ms, from the beginning of the conversation to its end. In this second respect, the current article also extends the work in [2], where predictions were made only at turn landmark locations. In addition, unlike the authors of [2], who compared their system to a random baseline, the current article compares the contribution of breathing in the context of multi-participant speech activity to a baseline trained on multi-participant speech activity alone.…”
Section: Introductionmentioning
confidence: 73%
“…There were also some indications that turn-initial inhalation was deeper than inhalations made later in the turn [4,5]; however, these findings were not confirmed by other studies [2], or were only observed in scripted dialogues [4]. By contrast, [2] found that inhalation tends to be deeper in turn-holding than in turn-changing pauses, although the size of this effect seemed to be rather small. By including an additional category of backchannel-like utterances in our own work we have been able to identify consistent variation in inhalation amplitude across turn-categories [3].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations